Novel EZH2 mutation in a patient with secondary B-cell acute lymphocytic leukemia after deletion 5q myelodysplastic syndrome treated with lenalidomide: A case report - Burgos, Sebastian (Medicine (Baltimore), 2019)
RATIONALE: The gene deletion (5)(q22q35) is reported in 10–20% of myelodysplastic syndrome (MDS) cases and is associated with response to lenalidomide and favorable prognosis. The authors report here a clinical case of MDS transformation to B-cell acute lymphocytic leukemia (B-ALL) with an associated accrual of an additional mutation following treatment with lenalidomide. PATIENT CONCERNS: A 69-year-old man presented with progressive anemia, normal white blood cell count, and thrombocytopenia consistent with MDS. He was administered lenalidomide for 27 months, then developed acute B-cell lymphocytic leukemia and acquired a previously unreported mutation in the gene enhancer of zeste homolog 2 (EZH2). DIAGNOSES: After 27 months of therapy with lenalidomide, a surveillance bone marrow aspiration (BMA) revealed 90% cellularity with persistent multilineage dysplasia and a population of blasts comprising 54% of all bone marrow elements by morphology, consistent with B-ALL, even though the patient was asymptomatic. Conventional karyotype showed no signs of del(5)(q22q35) MDS, however bone marrow next–generation sequencing (NGS) demonstrated the accrual of a nonsense mutation (c.211del pL71∗) in exon 3 of EZH2. A confirmatory BMA yielded 70% blasts and clinical features indicative of B-ALL. INTERVENTIONS: Mini-hyper-CVD (cyclophosphamide and dexamethasone at 50% dose reduction, no anthracycline, methotrexate at 75% dose reduction, cytarabine at 0.5 g/m(2) × 4 doses) was administered for 21 days. OUTCOMES: A follow-up BMA was performed 2 months after mini-hyper-CVD therapy, showing dysplastic features with 25% ring sideroblasts, but no evidence of B-ALL. The patient is currently receiving monthly-low dose decitabine, ofatumumab, and dexamethasone, and is transfusion independent and asymptomatic after 7 cycles. LESSONS: The present study shows an extremely rare progression of del(5)(q22q35) MDS to B-ALL with accompanying NGS data and a newly described acquisition of an EZH2 frameshift mutation. This case highlights the importance of NGS as a diagnostic and surveillance tool for MDS.